Analisis Penerapan Manajemen Sumber Daya Manusia, Disiplin Kerja, Serta Prestasi Kerja, Dalam perkembangan karir karyawan - Dhea Fadhila Fitri; Muhammad Najib Kasim; M. Yusuf Alfian Rendra Anggoro (BJRM (Bongaya Journal of Research in Management), 2025)
Abstract: Juan, this research is a type of quantitative study aimed at analyzing the Application of Human Resource Management, Work Discipline, and Work Performance in Employee Career Development. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the issues being researched to all employees of Bank BRI, Pattallassang Takalar unit. Data collection was conducted through observation and the distribution of questionnaires. In this study, the data sources used for data collection included primary and secondary data. The research instruments used for data collection were direct questionnaire distribution and Likert scale. Based on the research data results using calculations through the Statistical Package for the Social Sciences (SPSS) Version 26. Statistically, the results of the research indicate that Human Resource Management has no impact but has a significant effect on employee career development, work discipline has a positive and significant effect on employee career development, and work performance has a positive and significant effect on employee career development. Keywords: Work discipline, Work performance, Employee career development.